Field studies on the germination behaviour of black-grass (Alopecurus myosuroides Huds.) depending on sowing date und winter wheat variety in Northern Germany - Landschreiber, Manja (Julius-Kühn-Archiv, 2014)
Black-grass (Alopecurus myosuroides, Huds.) is the most important herbicide-resistant weed in Europe. In Germany it is not only a problem in the maritime influenced areas like Schleswig-Holstein and Lower Saxony anymore, as well in other regions black-grass develops to the most important weed in winter wheat and oilseed rape. There are multifaceted reasons for that, one reason are close winter crop rotations and early sowing dates which are economically very attractive for the farmers, another one are herbicide resistances. Black-grass germinates in autumn and in spring, but the main germination period is from late August to early October. If winter wheat is sown early in autumn, the main germination is in parallel to the wheat. Then the weeds can only be managed by culture specific herbicides. The pressure on the herbicides is therefore increasing. Herbicide resistances can be the result. As long as very effective herbicides are available, so that farmers are not dependent on weed biology and plant production weed management measures such as sowing date. Late sowing dates can reduce the black-grass populations, but this option is not attractive to many farmers in Schleswig-Holstein. In mind of the farmers the risk of delayed sowing dates in autumn is too high, because increased rainfall such as can make it difficult to marsh soils sowing, or make impossible. Objective of this trial was the germination of Black-grass to show to two sowing dates. The results of the field trial show, that black-grass populations can be reduced if winter wheat is sown later in autumn.